Bovine immunoprotection against Rhipicephalus (Boophilus) microplus with recombinant Bm86-Campo Grande antigen - Cunha,Rodrigo Casquero (2012)
The southern cattle fever tick, Rhipicephalus (Boophilus) microplus, is no doubt the most economically important ectoparasite of cattle globally. The inappropriate use of chemical acaricides has driven the evolution of resistance in populations of R. (B.) microplus. Anti-tick vaccines represent a technology that can be combined with acaricides in integrated control programs to mitigate the impact of R. (B.) microplus. The recombinant form of Bm86 antigen from the Campo Grande (rBm86-CG) strain of R. (B.) microplus was produced using the Pichiapastoris expression system to test its ability to immunoprotect cattle against tick infestation. Secretion of rBm86-CG by P. pastoris through the bioprocess reported here simplified purification of the antigen. A specific humoral immune response was detected by ELISA in vaccinated cattle. Immunoblot results revealed that polyclonal antibodies from vaccinated cattle recognized a protein in larval extracts with a molecular weight corresponding to Bm86. The rBm86-CG antigen showed 31% efficacy against the Campo Grande strain of R. (B.) microplus infesting vaccinated cattle. The rBm86-CG is an antigen that could be used in a polyvalent vaccine as part of an integrated program for the control of R. (B.) microplus in the region that includes Mato Grosso do Sul.